Michael Brown - HARNEY, Stephen Matthias (Institutional Knowledge at Singapore Management University, 2015)
How can we survive genocide? We can only address this question by studying how we have survived genocide. In the interest of imagining what exists, there is an image of Michael Brown we must refuse in favor of another image we don’t have. One is a lie, the other unavailable. If we refuse to show the image of a lonely body, of the outline of the space that body simultaneously took and left, we do so in order to imagine jurisgenerative black social life walking down the middle of the street—for a minute, but only for a minute, unpoliced, another city gathers, dancing. We know it’s there, and here, and real; we know what we can’t have happens all the time. Imagining what exists requires and allows analysis.